Pengaruh ekspresi Vascular Endothelial Growth Factors (VEGF) post-neoadjuvant kemoterapi terhadap respon kemoterapi (huvos), local recurrence, metastasis, dan survival pada pasien osteosarkoma - Kadek Ayu Candra Dewi (DiscoverSys Inc., 2019)
Background: Overexpression of VEGF before therapy has been associated with decreased survival and poor prognosis of osteosarcoma patients, but VEGF expression in osteosarcoma patients following receiving neoadjuvant chemotherapy has not been much elucidated. The purpose of this study was to determine the effect of VEGF expression after neoadjuvant chemotherapy on chemotherapy responses (HUVOS), local recurrence, metastases and survival of osteosarcoma patients.Methods: A cross-sectional study was conducted in Jakarta during the 2009-2010 period to 19 osteosarcoma patients at Cipto Mangunkusumo Hospital, Jakarta. Data on patient’s characteristics, VEGF expression after chemotherapy, local recurrence, metastasis, chemotherapy response and survival in osteosarcoma patients were recorded and analysed using statistical analysis. All data were analysed using SPSS software version 16 for Windows.Results: Most respondents were male (63.2%), age> 14 years (84.2%), stage IIB (94.7%), poor HUVOS (73.7%), size <10 cm (63, 2%), positive VEGF expression (57.9%), negative metastasis (73.7%), and death (73.7%). There was no significant relationship between VEGF expression and all parameters assessed (P> 0.05).Conclusion: VEGF expression by living osteosarcoma cells after neoadjuvant chemotherapy is not significantly related to histological response (HUVOS), local recurrence and metastasis, but has a significant relationship with good survival.